Whole exome sequencing with a focus on cardiac disease-associated genes in families of sudden unexplained deaths in Yunnan, southwest of China - Si-Jie Wei; Jin-Liang Du; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Zhong-Chun Sun; Xue Tang; Kai Liu; Yan-Mei Xi; Sheng-Jie Nie; Peng-Lin Jia; Wu Long; et al. (BMC Genomics, 2023)
Abstract Objectives To explore the causes of sudden unexpected death (SUD) and to search for high-risk people, whole exome sequencing (WES) was performed in families with SUDs.  Methods Whole exome sequencing of 25 people from 14 SUD families were screened based on cardiac disease-associated gene variants, and their echocardiograms and electrocardiograms (ECG) were also examined. The protein function of mutated genes was predicted by SIFT, PolyPhen2 and Mutation Assessor. Results In the group of 25 people from 14 SUD families, 49 single nucleotide variants (SNVs) of cardiac disease-associated genes were found and verified by Sanger sequencing. 29 SNVs of 14 cardiac disorder-related genes were predicted as pathogens by software. Among them, 7 SNVs carried by two or more members were found in 5 families, including SCN5A (c.3577C > T), IRX4 (c.230A > G), LDB3 (c.2104 T > G), MYH6 (c.3G > A), MYH6 (c.3928 T > C), TTN (c.80987C > T) and TTN (c.8069C > T). 25 ECGs were collected. In summary, 4 people had J-point elevation, 2 people had long QT syndrome (LQTS), 4 people had prolonged QT interval, 3 people had T-wave changes, 3 people had sinus tachycardia, 4 people had sinus bradycardia, 4 people had left side of QRS electrical axis, and 3 people had P wave broadening. Echocardiographic results showed that 1 person had atrial septal defect, 1 person had tricuspid regurgitation, and 2 people had left ventricular diastolic dysfunction. Conclusions Of the 14 heart disease-associated genes in 14 SUDs families, there are 7 possible pathological SNVS may be associated with SUDs. Our results indicate that people with ECG abnormalities, such as prolonged QT interval, ST segment changes, T-wave change and carrying the above 7 SNVs, should be the focus of prevention of sudden death.